Banana blossom-based vegan meat innovation: Food diversification and economic strengthening in Sambirejo Village - Zuhria, Siti Aminatuz; Puspaningrum, Yessita; Hartanti, Dyah Ayu Sri; Qomariyah, Siti Nur (Community Empowerment, 2025)
Optimizing agricultural by-products such as banana blossoms (Musa acuminata colla) is a crucial strategy to strengthen food security and rural economies. This community service program aims to enhance the capacity of PKK members in Sambirejo Village to produce banana blossom-based vegan meat as a local flagship product. The implementation methods included socialization, demonstrations, and hands-on training covering raw material management and processing technology. Evaluation of 25 participants using pre-test and post-test instruments showed significant improvements across all indicators. Average conceptual understanding increased from a moderate level (2.77) to high (3.50), while technical skills in processing technology recorded the highest growth (Δ = 0.80). These findings demonstrate that disseminating plant-based food technology effectively transforms local commodities into high-value economic products. The program recommends developing village micro-enterprises to ensure product sustainability as a pillar of self-reliant food security.